The effect of including agro-industrial by-products on the fermentation pattern of grass silage and the performance of sheep: a meta-analysis - Barbosa, Cristiane Rebouças [UNESP]; Torres, Rodrigo de Nazaré Santos [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Baldassini, Welder Angelo [UNESP]; Machado Neto, Otavio Rodrigues [UNESP]; Costa, Ciniro [UNESP] (Wiley, 2024)
The objectives of this study were to evaluate the effects of adding agro-industrial by-products (BP) on the fermentation pattern of grass silage (GS; objective 1) and on the performance of sheep (objective 2). Silage quality (dataset composed of 37 studies with 179 treatment means) was evaluated using the weighted mean difference (WMD) between the control (GS) and treatment (GS with BP) groups. Sheep performance (dataset composed of 7 studies with 23 treatment means) was evaluated using the WMD between the control diet (DGS = diet + GS without BP) and treatment diet (DGS-BP = diet + GS with BP). Treatment means were weighted by the inverse of the variance. The type of BP and harvest period of GS were the main covariates that influenced the effect of BP inclusion on the silage fermentation characteristics. The inclusion of BP in GS reduced pH, N-NH3, acetate, and butyrate and increased lactic acid concentration and lactic acid bacterial count. The type of BP and storage time were the main covariates that influenced the performance of sheep to DGS-BP. The DGS-BP inclusion in diet increased crude protein and neutral detergent fibre intake, total digestible nutrient digestibility, and the carcass weight of sheep.
Keywords: carcass; fruit by-product; Lamb; rumen; silage quality